Life cycle of the rove beetle, Atheta coriaria (Kraatz) (Coleoptera: Staphylinidae) and suitability as a biological control agent against the fungus gnat, Bradysia sp. nr. Coprophila (Lintner) - Echegaray Wilson, Erik Rubens (Kansas State University, 2012)
The life history of the rove beetle, Atheta coriaria (Kraatz) (Coleoptera:Staphylinidae), predation against the fungus gnat Bradysia sp. nr. coprophila (Lintner) and compatibility with pesticides and plant growth regulators was investigated under laboratory conditions using Sunshine LC1 Professional Growing Mix as a substrate. Duration of life stages was 2.2, 7.1, and 7.8 days for egg, larva and pupa respectively, at 26°C, whereas total development time from egg to adult was 17.0 days. In addition, A. coriaria male and female adult longevity was 60.3 and 47.8 days. Average fecundity was 90.2 eggs per female and the number of adults produced per female was 69.1. There were no significant differences in prey consumption when using second and third instar fungus gnat larvae as prey and starved and non-starved rove beetles. Overall, predation efficacy in Petri dishes was high (70 to 80%) as fungus gnat larval density increased with 3.9, 7.0, 11.1, and 15.3 larvae consumed in 24 hours after exposure of 5, 10, 15 and 20 fungus gnat larvae to one rove beetle adult. However, lower predation rates were found at different predator:prey ratios when using 1 to 5 rove beetles and growing medium as a substrate. The direct and indirect effects of pesticides and plant growth regulators on A. coriaria were investigated under laboratory conditions. Rove beetle survival was consistently higher when adults were released 24 hours after rather than before applying pesticides. Acetamiprid, lambda-cyhalothrin, and cyfluthrin were directly harmful to rove beetle adults, whereas Beauveria bassiana, azadirachtin and organic oils were compatible with A. coriaria. Similarly, the plant growth regulators acymidol, paclobutrazol and uniconazole were not harmful to rove beetle adults. In addition, Beauveria bassiana, azadirachtin, kinoprene, organic oils, and the plant growth regulators did not negatively affect A. coriaria development. However, Beauveria bassiana did negatively affect rove beetle prey consumption. This study demonstrated that A. coriaria is not compatible with the pesticides acetamiprid, lambda-cyhalothrin and cyfluthrin, whereas there is compatibility with organic oils, Beauveria bassiana, azadirachtin, and the plant growth regulators. As such, these compounds may be used in combination with A. coriaria in greenhouse production systems.
Keywords: Biological control; Atheta coriaria; fungus gnats; Entomology (0353)